New Propaganda Model: Pertarungan Wacana Politik dalam Bisnis Media - Puji Hariyanti (Program Studi Ilmu Komunikasi, 2006)
Propaganda in broadest sense is the technique of influencing human action by manipulation of representations. Mass media is the most effective tools to do this. Politics and economics interest use mass media to establish their power. Their policy influences content of mass media and make it was not objective. This phenomenon was indicated as new propaganda models.